Futurism and Experimentation in Italian Theater in the Late 20th Century (Itinera, 2012)
This paper aims to understand whether and to which extent the Futurism theory of theatre and its practices have influenced the Italian contemporary scene. Common opinion still has it that Futurism has left little to no legacy in the Italian theatre, and we cannot properly speak of neo-futurism or of an active Futurist avant-garde. Nonetheless, taking a closer look at some of most significant figures in Italian experimental theatre (for example, Ivrea Manifesto’s project, Carmelo Bene, Socìetas Raffaello Sanzio) this paper aims to underline the many elements that trace back to Futurist’s theatre, suggesting the need to re-read futurist artistic experiences – at least in the field of performing arts – as constructive practices aimed at the building of a new kind of theatre.